GAMBARAN TINGKAT KECEMASAN IBU TERHADAP ANAK EPILEPSI DI RUMAH SAKIT MEURAXA BANDA ACEH - Mursyida Mursyida; Rahmil Izzati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Epilepsy is one of the most common causes of morbidity in the child's nervous system, leading to problems such as learning difficulties, growth disorders, and quality of life. Epilepsy is a brain disorder with a variety of etiologies but with a single unique symptom, ie recurrent seizures caused by electrical neuro cortical charge disorders. Concerns and anxiety experienced by parents will affect the physical aspects of parents, physical responses in the parents can be shaking, dyspepsia, anorexia and sleep disorders, physical disorders can occur due to a problem on the psychological aspects of a person, in addition to aspects physical, parental anxiety can also affect the aspects of parental behavior. The purpose of this research is to know the description of maternal anxiety level on epilepsy at Meuraxa Hospital, Banda Aceh 2018. The research method used descriptive cross sectional with sampling by accident sampling and fulfilling inclusion and exclusion criteria. The age result based on 14 respondents was 25 - 30 years (42.9%), 31 - 35 years (50%) and 36 - 40 years (7.1%). Results were based on education of elementary school students (0%), junior high (7.14%), high school (35.72%), and college (57.14%). Results based on respondents' work were found by respondents who worked (78.57%), and those who did not work (21.43%). The result of the anxiety level of the respondents was obtained from normal anxiety level (0%), mild (0%), moderate (35.71%), heavy (42.86%) and very heavy (21.43%).Keywords: Epilepsy, Maternal Anxiety Level, Meuraxa Hospital